Sustaining statehood: A comparative analysis of vertical policy-process integration in Denmark and Italy - Christoph Knill; Christina Steinbacher; Yves Steinebach (Public Administration, 2021)
In response to societal demands, democratic governments constantly adopt new policies. As existing policies are rarely abandoned, policies accumulate over time. Policy accumulation bears the challenge of overburdening implementation bodies, hence undermining policy effectiveness. Any escape from this situation requires democratic governments to strike a balance between policy responsiveness and effectiveness. We posit that the extent to which countries are able to achieve this depends on the vertical integration of processes of policy formulation and implementation. We provide a novel conceptualization of vertical policy-process integration (VPI) that is based on two channels. While bottom-up integration captures the extent to which policy implementers can communicate reasons for potential policy failure from the bottom up, top-down integration indicates the degree to which the policy formulation level has to cover the implementation costs of the policies they produce. We illustrate our argument by an empirical analysis of VPI patterns in Denmark and Italy.
Keywords: 340